Inhibition of autophagy enhances the antitumor efficacy of T/CAR T cell against neuroblastoma - Francesca De Mitri; Manuela Giansanti; Ombretta Melaiu; Dorothee Haas; Stefan Ebert; Nicola Tumino; Elisabetta Vulpis; Francesca Gatto; Beatrice Martuscelli; Manuela Antonioli; Elisabetta Sangiuliano; Simona Caruso; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract Neuroblastoma (NB) is the most common extracranial solid tumor in children characterized by poor immune infiltration and resistance to adaptive immunity, contributing to its limited response to immunotherapy. A key mechanism underlying immune evasion in cancer is autophagy, a cellular process that plays many roles in cancer by supporting tumor survival and regulating immune interactions. In this study, we investigate the impact of autophagy inhibition on NB tumor growth, immune modulation, and the efficacy of immunotherapy. Using both murine and human NB cell lines, we demonstrate that genetic and pharmacological inhibition of autophagy significantly reduces 3D spheroid growth and upregulates major histocompatibility complex class I (MHC-I) expression. In vivo studies further confirm that targeting autophagy suppresses tumor progression and promotes immune infiltration into the tumor. Notably, we observe a significant increase in CD8+ T cell recruitment and activation, suggesting that autophagy inhibition reshapes the immune landscape of NB, rendering it more susceptible to immune-mediated clearance. Crucially, autophagy inhibition also sensitizes NB cells to T cell-mediated cytotoxicity and enhances the therapeutic efficacy of GD2.CAR T-cell therapy. In vitro co-culture assays reveal increased CAR T cell-mediated tumor killing upon autophagy blockade, while in vivo models show prolonged tumor control and improved survival in treated mice compared to CAR T-cell therapy alone. These findings highlight autophagy as a key regulator of immune evasion in NB and suggest that its inhibition could serve as a promising therapeutic strategy to enhance immune recognition and improve the efficacy of immunotherapy.